(3GdJYHjQ aj Yde GdJaUjd aj WQjb Gddg JYGdis - (3GdbTJGdj , eMeO Hf TYjH Hf eMeO GdMLGRj GdTYjHj GdGHTjgj,J (B1035 (3g` s
(3ChdgG (B:s
(3hHYO aEf Gddg JYGdi LYd dgPg GdWQjb GdeSJbjeI OGdI Ydjg hehUdI Edjg hPdc Ydi jO ef jTGA ef YHGOg ai LejY CQVg hHdGOg s
(3BNQgG (B:s
(3eMhJ GHfj hRGdJ fbWI GdZjf hgPG BNQ eG aJM Gddg Hg aj gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3hjdjg bUGFO dg CjVkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B295s
Keywords: (3GdJUha hGdBOGH GdTQYjIs